Técnicas de asistencia para la recuperación de la locomoción funcional después de una lesión de médula espinal - Villanueva, D.; Muñoz, R.; Hernández, P. R. (Revista Mexicana de Ingenieria Biomedica, 2001)
A review of applied techniques for recovering functional locomotion of patients with spinal cord injury (SCI) is presented in this work. Availability, performance, and limitations are considered in the analysis. Efforts, over the last 30 years, directed to rehabilitation of patients suffering an SCI, can be grouped as: passive orthosis, active orthosis, functional electrical stimulation (FES), hybrid orthosis (FES and passive orthosis) and gait retraining. At the present time, a passive orthosis is the available option for holding a vertical position and for partially recovering the functional locomotion. The main challenge in clinics is to face the high rejection for a continuous use of an orthosis after a submission to training and rehabilitation. The areas for developing future works offer autonomous locomotion, a reduction in metabolic cost and the incorporation of new actuators with high power density to reduce weight without diminishing power. Hybrid systems using active orthosis have been rarely involved. However, this could be an option that could take advantage from FES systems and active orthosis. Systems for locomotive training with body partially supported, have demonstrated to be considered an excellent option for recovering the functional locomotion. Some authors report important benefits of patients with incomplete SCI submitted to this treatment. For futures works, designers must focus their task covering the needs of customers mainly thinking in functional benefits.